Peculiarities of Using Different Forms of Work as for Overcoming Manifestations of Deadaptation of the Future Tutors in Higher Educational Establishment - Zdanevych, Larysa (Pedagogical Discourse, 2014)
Analysis of different forms of pedagogical work as for overcoming deadaptation of the future teachers in higher educational establishment has been done in the article. Peculiarities of the phenomenon of adaptation-deadaptation of teenagers in different spheres of psychological-pedagogical science, problems of teenagers have been revealed, it is mentioned that at the modern period deadaptation is understood as a combination of features and manifestations, which prove non-conformity of interaction of a person with the environment. Some characteristics of social status of a student of the first year of study have been determined. The essence of such status can be mastering the norms and functions of the future professional activity. Different features of the social status can be: realizing of the new quality in its social position, rising of the feeling of own dignity; striving for consolidation in this new position; striving for achieving first success, which proves new, higher position; interest and diligence in performing educational and other work in pedagogical higher educational establishment; variety of educational and out-of-class interests. The approaches as for the influence of the factors (educational, family, environmental, somatic, psychological, age, corrective-preventive) to the social deadaptation have been analyzed, brief characteristic of the mentioned phenomenon has been given. The program of special course for teachers and curators of academic groups as for preventing manifestations of deadaptation of the students of the first year of study and acceleration of their adaptation has been created and described.